Computer information technology modeling tribological systems - Sorokatyi, R.; Dykha, A.; Pasichnyk, O.; Skrypnyk, T. (Problems of Tribology, 2020)
It has been proposed to use the triboelement method to improve the elements of information technology CAD / CAM / CAE - tribological systems. The method uses a unified mathematical apparatus and a methodological approach in modeling wear of various types of friction units and takes into account the requirements for the mathematical support of CAD / CAM / CAE systems. The mathematical support of information technology and the generalized algorithm for the interaction of the wear calculation module with the elements of CAD / CAM / CAE - systems have undergone sufficient testing through the implementation of software and verification of the calculation results.